Differentiation of Serous and Non-serous Epithelial Ovarian Cancer by Radiological Imaging - Yudistiarta, Devina; Dhamiyati, Wigati; Choridah, Lina (http://dharmais.co.id/, 2024)
Background: Ovarian cancer has a high incidence and fatality rate, with the most prevalent type is epithelial origin. The serous subtype of epithelial cancer predominates. For therapy selection, it is important to differentiate this subtype by histopathological examination as a gold standard method. Since some patients are not eligible for a biopsy, radiological modalities such as Magnetic Resonance Imaging (MRI) are superior in discriminating tissue compared to computed tomography (CT) or ultrasound. The use of the T1 weighted imaging (T1WI) and T2WI sequences can best differentiate between a cystic and a solid lesion. The goal of this study was to use radiological examination to assist in the identification of ovarian cancer.Methods: This cross-sectional study used secondary data from histopathology and MRI results from patients with ovarian cancer. Data was gathered utilizing electronic medical records in Dr. Sardjito Hospital between January 2017 and May 2022. The following MRI characteristics are evaluated including ascites, papillary projection, solid nodule, signal intensity of solid and cystic components, size, configuration, enhancement of contrast, and bilateral of the lesion.Results: Thirty-eight subjects made up the study’s sample, and 63% of them had serous subtypes. Bilateral lesion suggested a three times greater likelihood that it was serous ovarian cancer (p 0.02; binary logistic regression). Age 50 years old and strong enhancement on contrast was also relevant for separating the serous subtype from other subtypes (enhancement p 0.02; age p 0.044). Conclusions: A bilateral lesion with a significantly enhanced pattern can be seen on the MRI of a serous subtype of epithelial ovarian cancer. The elderly are also more likely to develop this cancer.